Distribution of Chelus fimbriata and Chelus orinocensis (Testudines: Chelidae) - Cunha, Fábio A.G.; Fagundes, Camila K.; Brito, Elizângela S.; Vogt, Richard C.; Maffei, Fábio [UNESP]; Pezzuti, Juarez; Félix-Silva, Daniely; Rojas-Runjaic, Fernando J.M.; Lasso, Carlos A.; Morales-Betancourt, Monica A.; De Carvalho, Vinicius Tadeu; Do Amaral, João Valsecchi; et al. (Chelonian Conservation and Biology Journal, 2021)
The matamatas (Chelus fimbriata and the recently described Chelus orinocensis) are the largest species in the family Chelidae, easily identified by their distinct morphological characteristics. The matamatas have a wide distribution in South America, occurring in Bolivia, Brazil, Colombia, Ecuador, Guyana, French Guiana, Peru, and Venezuela, as well as Trinidad and Tobago. However, there are many gaps in the knowledge of its distribution. The objective of this study was to present new records of occurrence for the C. fimbriata species complex and describe the area of distribution. We compiled data from published papers, databases in museums and other scientific collections, and research institutes and conservation organizations. From these data we mapped the species distribution, considering 3 types of river drainages based on water color in the Amazon Basin. We added 182 new records in Brazil, Venezuela, Colombia, Bolivia, and Peru, demonstrating that the C. fimbriata species complex has a wide distribution, totaling 6,907,551 kmacross all 3 river types. Most records were concentrated in areas lower than 200 m above sea level.
Keywords: Amazon basin; Chelidae; matamata; natural history; Orinoco; river types; species complex; water color